Heparin bridging in warfarin anticoagulation therapy initiation could increase bleeding in non‐valvular atrial fibrillation patients: a multicenter propensity‐matched analysis. (7th January 2015) - Kim, T.‐H.; Kim, J.‐Y.; Mun, H.‐S.; Lee, H.‐Y.; Roh, Y. H.; Uhm, J.‐S.; Pak, H.‐N.; Lee, M.‐H.; Joung, B.
Summary Background The efficacy of heparin‐bridging therapy during the initiation of oral anticoagulation therapy (OAC) in non‐valvular atrial fibrillation (NVAF) is unclear. Objectives To evaluate the efficacy and the safety of heparin‐bridging therapy during OAC initiation in NVAF patients. Patients/Methods This study included 5327 consecutive warfarin‐naïve NVAF patients who received OAC that was initiated with (n = 1053) or without (n = 4274) heparin bridging at four tertiary hospitals. Stroke and bleeding events within 30 days of OAC were evaluated. Results While there was no difference in the incidence of stroke (0.5% vs. 0.3%, P = 0.381), major bleeding rate (0.9% vs. 0.3%, P = 0.004) was higher in heparin‐bridged than in non‐bridged patients. This trend remained in the propensity score–matched population (stroke 0.5% vs. 0.6%, P = 0.762; major bleeding 0.8% vs. 0.1%, P = 0.019). A high CHA2DS2‐VASc score was an independent predictor for stroke, whereas bridging therapy had no beneficial effect in preventing stroke regardless of CHADS2 or CHA2DS2‐VASc scores. The HAS‐BLED score had a predictive value for major bleeding (odds ratio 1.80, 95% confidence interval 1.11–2.92, P = 0.018), and heparin‐bridging therapy was associated with a higher major bleeding rate (odds ratio 4.44, 95% confidence interval 1.68–11.72, P = 0.003), especially in patients with a HAS‐BLED score of ≥ 1. Conclusions The heparin‐bridging therapy increased bleeding without the benefit of preventing stroke at the initiation of OAC in NVAF. Our data suggest that heparin bridging should not be considered at the initiation of OAC in NVAF patients.